2012
DOI: 10.3201/eid1812.120929
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71–associated Hand, Foot, and Mouth Disease, Southern Vietnam, 2011

Abstract: We prospectively studied 3,791 children hospitalized during 2011 during a large outbreak of enterovirus 71–associated hand, foot, and mouth disease in Vietnam. Formal assessment of public health interventions, use of intravenous immunoglobulin and other therapies, and factors predisposing for progression of disease is needed to improve clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
113
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 12 publications
4
113
4
5
Order By: Relevance
“…In Taiwan, phylogenetic analyses revealed that different predominant genotypes occurred in 1998 (C2), 2000–2001 (B4), 2004–2005 (C4), and 2008 (B5) [10], [18]. This genotype replacement has also been observed in Malaysia and Vietnam [10], [19], [20]. Therefore, continuous monitoring genetic and antigenic evolution of EV71 are critical to vaccine development and epidemic control.…”
Section: Introductionmentioning
confidence: 97%
“…In Taiwan, phylogenetic analyses revealed that different predominant genotypes occurred in 1998 (C2), 2000–2001 (B4), 2004–2005 (C4), and 2008 (B5) [10], [18]. This genotype replacement has also been observed in Malaysia and Vietnam [10], [19], [20]. Therefore, continuous monitoring genetic and antigenic evolution of EV71 are critical to vaccine development and epidemic control.…”
Section: Introductionmentioning
confidence: 97%
“…Transmission occurs from person to person through direct contact with saliva, feces, vesicular fluid, or respiratory droplets of an infected person, and indirectly by contaminated articles [4]. Over the last decade, many large outbreaks of HFMD have been reported in countries of the Western Pacific Region, including Japan, Malaysia, Taiwan, Singapore, Vietnam, mainland China, and Cambodia [5][6][7][8][9][10][11]. HFMD is a major public health problem in China, resulting in 7.2 million clinical cases and 2,457 deaths from 2008 to 2012 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although HFMD is usually mild and self-limiting, neurological manifestations that are associated with systemic features, such as severe pulmonary edema and shock, can occur and occasionally lead to death. Since 1997, there have been a number of outbreaks of EV71-associated HFMD reported in Malaysia (1997 [1], 2000, and 2005 [2]), Taiwan (1998 [3]), Singapore (2000 [4]), Vietnam (2005 [5] and 2011 [6]), and China (2008 [7]). In China, since HFMD was listed in 2008 as a category C notifiable disease, the numbers of annual cases of HFMD that were reported from the Chinese National Infectious Disease information management system ranged between 1.16 and 1.92 million during 2009 to 2012 (http://www.chinacdc.cn/tjsj/fdcrbbg).…”
mentioning
confidence: 99%